Evaluation of Antioxidants and Antimicrobial Properties of Indigenous Plants: Elaeocarpus sphaericus and Ficus religiosa - Koirala, Barsha; Pakuwal, Evance; Rai, Hookman Jimi; Shrestha, Angela (International Journal of Environment, 2021)
Elaeocarpus sphaericus (Rudraksha) and Ficus religiosa (Peepal) are the two different indigenous and religious plants found in Nepal. These plants are rich in antimicrobial as well as anti-inflammatory properties. The present study was done to determine the antioxidants, anti-microbial properties, as well as to analyze the various phytochemicals found in the methanolic extracts of leaves of the sampled plants. The Antioxidants levels were determined by the DPPH Scavenging Assay. The methanolic extracts of the plants showed antioxidant properties i.e., 98.01 and 122.3 μg/ml for Rudraksha and Peepal, respectively. Likewise, the Antibiotic Susceptibility test was performed by Well-Diffusion assay in Mueller Hinton agar (MHA) plates. The zone of inhibition against the Gram-negative (Escherichia coli, Pseudomonas aeruginosa), and Gram-positive (Staphylococcus aureus, and Bacillus cereus) bacterial isolates were observed, supporting the antimicrobial activity of the plant. Additionally, various qualitative tests were performed for determining the presence/absence of the phytochemicals. Both Peepal and Rudraksha extracts gave positive tests for Flavonoids, Terpenoids, Cyclic glycosides, volatile oils, tannins, flavonoids, phenols, anthraquinone, glycosides, alkaloids, steroids, and reducing sugars, and phenols. Likewise, Saponins were found to be positive only in Peepal extracts with negative result for Phlabotannins and proteins. Thus, this research will help for utilizing the two religiously important plants i.e. Rudraksha and Peepal, for further researches in the medical field and preparation of various ayurvedic medicines.